POLÍTICA EDITORIAL E ESCOPO DA REVES - Antonio Marcos de Oliveira Siqueira; Wagner dos Reis Marques Araujo; Aldair Oliveira de Andrade; Roberta Ferreira Coelho de Andrade (REVES - Revista Relações Sociais)
POLÍTICA EDITORIAL E ESCOPO DA REVES